Genome-wide identification and expression profile analysis of nuclear factor Y family genes in Sorghum bicolor L. (Moench). - P Maheshwari; Divya Kummari; Sudhakar Reddy Palakolanu; U Nagasai Tejaswi; M Nagaraju; G Rajasheker; G Jawahar; N Jalaja; P Rathnagiri; P B Kavi Kishor (PLoS ONE, 2019)
Members of the plant Heme Activator Protein (HAP) or NUCLEAR FACTOR Y (NF-Y) are trimeric transcription factor complexes composed of the NF-YA, NF-YB and NF-YC subfamilies. They bind to the CCAAT box in the promoter regions of the target genes and regulate gene expressions. Plant NF-Ys were reported to be involved in adaptation to several abiotic stresses as well as in development. In silico analysis of Sorghum bicolor genome resulted in the identification of a total of 42 NF-Y genes, among which 8 code for the SbNF-YA, 19 for SbNF-YB and 15 for the SbNF-YC subunits. Analysis was also performed to characterize gene structures, chromosomal distribution, duplication status, protein subcellular localizations, conserved motifs, ancestral protein sequences, miRNAs and phylogenetic tree construction. Phylogenetic relationships and ortholog predictions displayed that sorghum has additional NF-YB genes with unknown functions in comparison with Arabidopsis. Analysis of promoters revealed that they harbour many stress-related cis-elements like ABRE and HSE, but surprisingly, DRE and MYB elements were not detected in any of the subfamilies. SbNF-YA1, 2, and 6 were found upregulated under 200 mM salt and 200 mM mannitol stresses. While NF-YA7 appeared associated with high temperature (40°C) stress, NF-YA8 was triggered by both cold (4°C) and high temperature stresses. Among NF-YB genes, 7, 12, 15, and 16 were induced under multiple stress conditions such as salt, mannitol, ABA, cold and high temperatures. Likewise, NF-YC 6, 11, 12, 14, and 15 were enhanced significantly in a tissue specific manner under multiple abiotic stress conditions. Majority of the mannitol (drought)-inducible genes were also induced by salt, high temperature stresses and ABA. Few of the high temperature stress-induced genes are also induced by cold stress (NF-YA2, 4, 6, 8, NF-YB2, 7, 10, 11, 12, 14, 16, 17, NF-YC4, 6, 12, and 13) thus suggesting a cross talk among them. This work paves the way for investigating the roles of diverse sorghum NF-Y proteins during abiotic stress responses and provides an insight into the evolution of diverse NF-Y members.